Factors Affecting Time to Surgery in Breast Cancer Patients. Issue 4 (April 2022) - Chagpar, Anees B.; Howard-McNatt, Marissa; Chiba, Akiko; Levine, Edward A.; Gass, Jennifer S.; Gallagher, Kristalyn; Lum, Sharon; Martinez, Ricardo; Willis, Allric I.; Fenton, Andrew; Solomon, Naveenraj L.; Senthil, Magi; et al.
Background: We sought to determine factors affecting time to surgery (TTS) to identify potential modifiable factors to improve timeliness of care. Methods: Patients with clinical stage 0-3 breast cancer undergoing partial mastectomy in 2 clinical trials, conducted in ten centers across the US, were analyzed. No preoperative workup was mandated by the study; those receiving neoadjuvant therapy were excluded. Results: The median TTS among the 583 patients in this cohort was 34 days (range: 1-289). Patient age, race, tumor palpability, and genomic subtype did not influence timeliness of care defined as TTS ≤30 days. Hispanic patients less likely to have a TTS ≤30 days ( P = .001). There was significant variation in TTS by surgeon ( P < .001); those practicing in an academic center more likely to have TTS ≤30 days than those in a community setting (55.1% vs 19.3%, P < .001). Patients who had a preoperative ultrasound had a similar TTS to those who did not (TTS ≤30 days 41.9% vs 51.9%, respectively, P = .109), but those who had a preoperative MRI had a significantly increased TTS (TTS ≤30 days 25.0% vs 50.9%, P < .001). On multivariate analysis, patient ethnicity was no longer significantly associated with TTS ≤30 ( P = .150). Rather, use of MRI (OR: .438; 95% CI: .287-.668, P < .001) and community practice type (OR: .324; 95% CI: .194-.541, P < .001) remained independent predictors of lower likelihood of TTS ≤30 days. Conclusions: Preoperative MRI significantly increases time to surgery; surgeons should consider this in deciding on its use.